2006
DOI: 10.1021/ol061858h
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Multicomponent-Coupling Reactions Involving a Carborhodation−Cross-Coupling Sequence

Abstract: [reaction: see text] A rhodium-catalyzed multicomponent-coupling reaction has been developed that involves a cross-coupling with organohalides as part of the reaction sequence. Through several experiments toward mechanistic investigations, it has also been demonstrated that the reaction most likely proceeds via a carborhodation-oxidative addition-reductive elimination pathway, which clearly contrasts to the corresponding palladium-catalyzed processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Nucleophilic addition with a Grignard reagent resulted in diminished diastereoselectivity, probably due to the chelation of the organomagnesium reagents (entry 10). The addition of MeZnCl, prepared from ZnCl 2 and LiBr‐free MeLi, was also attempted; however, a low chemical yield and diastereomeric ratio were observed (7 % yield, syn : anti =81:19) along with 67 % of unreacted 14 (entry 11). The polarity of solvent was also important in this reaction; less polar solvent systems such as THF/Et 2 O resulted in slightly lower diastereoselectivities ( syn : anti =84:16, entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…Nucleophilic addition with a Grignard reagent resulted in diminished diastereoselectivity, probably due to the chelation of the organomagnesium reagents (entry 10). The addition of MeZnCl, prepared from ZnCl 2 and LiBr‐free MeLi, was also attempted; however, a low chemical yield and diastereomeric ratio were observed (7 % yield, syn : anti =81:19) along with 67 % of unreacted 14 (entry 11). The polarity of solvent was also important in this reaction; less polar solvent systems such as THF/Et 2 O resulted in slightly lower diastereoselectivities ( syn : anti =84:16, entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, current methods often suffer from poor selectivity toward monoarylation, leading to decreased yields. 4 To circumvent these problems, we sought to develop an alternative α-arylation strategy with a broader scope and applicability.…”
mentioning
confidence: 99%
“…According to a hypothetic, yet plausible, catalytic cycle, this domino reaction most probably proceeds by either a stepwise or a concerted addition of an initially Hayashi et al [114] also reported the possibility of an intermolecular carbometallation of alkynes with arylrhodium species. Thus, it was confirmed experimentally that the formation of N-heterocyclic amides 400 was most probably initiated by an intermolecular carborhodation of the triple bond in 399 to yield the intermediate 401 (Scheme 10.137).…”
Section: Carbometallation Of Alkynes 845mentioning
confidence: 99%
“…R = n -Bu, i -Pr, (CH 2 ) 3 OMe, Ph R 1 = Me, Ph, m -Tol, ρ-MeOC 6 H 4 , Scheme 10.137 Rhodium-catalyzed arylation/cross-coupling reaction initiated by an intermolecular carborhodation step[114]. (R 2 ) 3 Al (1.0-2.0 equiv.)…”
mentioning
confidence: 99%